EVALUATION AND DESIGN OF MANAGEMENT INFORMATION SYSTEM DEVELOPMENT IN COMPLETENESS OF RECIPE SCREENING IN AR-RASYID ISLAMIC HOSPITAL PALEMBANG - Azzahra, Nia; P, Jason Merari; Saptarini, Opstaria; Wahab, Sabda (Universitas Muhammadiyah Magelang, 2023)
Errors in prescribing and administering drugs are things that often occur in medicine, so in an effort to improve pharmaceutical performance, an evaluation and development of a SIM is carried out to support pharmaceutical services in hospitals. The aim of this research is to evaluate the Management Information System needs at RSI Ar-Rasyid Palembang and continue with the development of a design model. This research is descriptive research conducted through direct observation and documentation. The development of this research system uses a prototype method starting from needs analysis, system design and implementation of the EUCS (End User Computing Satisfaction) framework system, creating a system design using context diagrams, Data Flow Diagrams and Entity Relationship Data, the data analysis method used is qualitative analysis. The results of the research from direct observation on the completeness of the IFRS SIM show that the SIM at RSI Ar-Rasyid in pharmaceutical screening has been fulfilled, but in administrative screening and clinical screening it has not been fulfilled and the results of evaluation using a questionnaire distributed to pharmaceutical installation staff show an average the answer to each statement variable is satisfied. In making a draft design, there are suggestions that include clinical screening of prescriptions, it is hoped that this will help pharmacy installation staff in providing services to avoid medication errors. Based on system design, input design and output design, the patient prescription screening management information system design meets the criteria so it is ready to be implemented into the system.